THE LEVEL OF CRITICAL THINKING SKILL ON SOLVING TWO-DIMENSIONAL ARITHMETICS PROBLEMS THROUGH RESEARCH-BASED LEARNING - Suntusia Suntusia; Dafik Dafik; Hobri Hobri (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Developing critical and collaborative thinking skills among learners was of significant importance in the 21st-century era. In this study, the researcher applied teaching and learning based on Research-Based Learning (RBL) to know the level of students critical thinking skill. The number of research samples was 30 students. This study used a triangulation research method, namely a combination of qualitative and quantitative methods. The quantitative method was obtained by using a learning outcome test and the qualitative method is obtained using a questionnaire and interview. Then the data that has been collected was analyzed using a t-test. Four students were chosen to represent critical thinking level 4, 13 students were chosen to represent Critical Thinking level 3, and 6 students were chosen to represent critical thinking level 2, 4 students were chosen to represent critical thinking level 1, and 3 students were chosen to represent critical thinking level 0. More subjects would be involved until the data was saturated. Students on low critical thinking were at Level 0. Based on the interpretation result of the t-test value, there was a significant difference between the control class and the experimental class, proved by the 0.000 figure in the statistical analysis. Therefore, it proved a significant difference in learning outcomes. However, the data that we obtained present a significant difference between the control class and the experimental class below 0.05. After we interpreted t-tabel = 2.04 on degrees of freedom 0.025, t-count of 0.000 was evident. Thus, a hypothesis was accepted since it was below 0.025. Qualitative methods show the results of interviews with 2 students.